The use of essential oils in the treatment of malasseziasis in dogs and cats: Review - Sousa, Andrade Sousa (Pubvet, 2020)
Malasseziasis is a common fungal skin disease of humans and animals, caused by the lipophilic yeast Malassezia pachydermatis. Treatment is based on the association between systemic and topical antifungal; however, recurrences are frequent and complicated by intercurrent dermatoses that complicate the clinical case. This recurrence is usually due to errors in dosage of the drugs, administration of the same by owners and resistance of the yeast. The mechanisms of antifungal resistance are associated with the specific or acquired characteristics of the pathogen to the drugs. As an alternative to traditional treatments, the use of herbal products, such as essential oils, in the veterinary clinic has become popular. Although the possible action of essential oils has been reported in human medicine for about 17 years, the specialized literature on its use in canine and feline malasseziasis is still scarce and studies are needed to investigate the mechanisms of action of essential oils in the metabolism of the yeast Malassezia pachydermatis. Thus, the objective of this work is to present a bibliographic review on the use of four essential oils for the treatment of primary or secondary malasseziasis in dogs and cats.
Keywords: Animal phytotherapy; essential oils; external otitis; malasseziosis